Crime and crime control in an integrating Europe: plenary presentations held at the Third Annual Conference of the European Society of Criminology, Helsinki 2003 - Aromaa, Kauko; Nevala, Sami (Publication series, 2004)
The theme of the conference was “Crime and Crime Control in an Integrating Europe”. Relating to this, the plenary presentations cover topical issues of European integration, crime, and criminal policy, including the enlargement process of the European Union.